2011
DOI: 10.1371/journal.pntd.0001343
|View full text |Cite
|
Sign up to set email alerts
|

Managing Tsetse Transmitted Trypanosomosis by Insecticide Treated Nets - an Affordable and Sustainable Method for Resource Poor Pig Farmers in Ghana

Abstract: An outbreak of tsetse-transmitted trypanosomiasis resulted in more than 50% losses of domestic pigs in the Eastern Region of Ghana (source: Veterinary Services, Accra; April 2007). In a control trial from May 4th–October 10th 2007, the efficacy of insecticide-treated mosquito fences to control tsetse was assessed. Two villages were selected – one serving as control with 14 pigsties and one experimental village where 24 pigsties were protected with insecticide treated mosquito fences. The 100 cm high, 150denier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…Bauer et al (2011) reported a significantly lower incidence of trypanosome infections and thus higher PCV in animals protected by Zero fly fences than in controls. Apart from their role in transmission of Trypanosomes, tsetse and other biting flies can cause high level of annoyance and blood loss, and affect feeding patterns of animals, thus resulting in reduced weight gain, decreased milk production, and animal performances (Byford et al, 1982;Mullens et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Bauer et al (2011) reported a significantly lower incidence of trypanosome infections and thus higher PCV in animals protected by Zero fly fences than in controls. Apart from their role in transmission of Trypanosomes, tsetse and other biting flies can cause high level of annoyance and blood loss, and affect feeding patterns of animals, thus resulting in reduced weight gain, decreased milk production, and animal performances (Byford et al, 1982;Mullens et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In Ghana, impregnated mosquito nets were used to protect cattle pens but also reduced significantly mosquito malaria vectors (Anopheles gambiae Giles and Anopheles ziemanni Grunberg; Diptera: Culicidae) (Maia et al 2012). In Ghana, treated fences have been proved to be very efficient to protect pigs pen against tsetse (Bauer et al 2011). It was also successfully used in Guinea in older non active human African trypanosomosis (HAT) foci to reduce vector densities and prevent HAT transmission (Kagbadouno et al 2011).…”
Section: Insecticide Treated Fencesmentioning
confidence: 99%
“…Tsetse flight patterns (short flights, successive and low height Leak, 2009;Bouyer, 2009) are a strategy for tsetse to save energy resources. This strategy was exploited to design various control techniques such as insecticide footbaths (Bouyer et al, 2007c(Bouyer et al, , 2008 or 1-m height insecticide fences around the cattle or pig pens (Bauer et al, 2011;Kagbadouno et al, 2011).…”
Section: Vertical Distributionmentioning
confidence: 99%
“…Understanding this particular behaviour contributed to the development of visual lures (traps and targets) which, to be effective, must be set just above the ground (20-45 cm). Protection of livestock with only 1-m high insecticide-treated mosquito nets (ITN) around enclosures are based on the same principle (Kagbadouno et al, 2011;Bauer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%